Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ma13051251
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Composite Flame Retardants for Improving the Flame Retardancy, Thermal Stability, Smoke Suppression, and Mechanical Properties of EVA

Abstract: Ethylene vinyl acetate (EVA) copolymer has been used extensively in many fields. However, EVA is flammable and releases CO gas during burning. In this work, a composite flame retardant with ammonium polyphosphate (APP), a charring–foaming agent (CFA), and a layered double hydroxide (LDH) containing rare-earth elements (REEs) was obtained and used to improve the flame retardancy, thermal stability, and smoke suppression for an EVA matrix. The thermal analysis showed that the maximum thermal degradation temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This is due to liberation of phosphoric acid, which promotes the formation of char. The burning of sample (d) also left a signi cant amount of "clear" char, which comes from the present metallic sodium, which in turn produces the sodium oxides that change the appearance of the char layer (Liu et al 2020). * pHRR = The amount of heat liberated at the peak of the heat release rate curve; tpHRR = The time when the pHRR is reached; ti = the time to ignition, once subjected to a ame; te = The time to extinction of the ame; ttf = Total time of re (from ignition to extinction) (ttf = te -ti); THR = The total heat released from ignition to extinction of the ame.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to liberation of phosphoric acid, which promotes the formation of char. The burning of sample (d) also left a signi cant amount of "clear" char, which comes from the present metallic sodium, which in turn produces the sodium oxides that change the appearance of the char layer (Liu et al 2020). * pHRR = The amount of heat liberated at the peak of the heat release rate curve; tpHRR = The time when the pHRR is reached; ti = the time to ignition, once subjected to a ame; te = The time to extinction of the ame; ttf = Total time of re (from ignition to extinction) (ttf = te -ti); THR = The total heat released from ignition to extinction of the ame.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, LDHs need to be modified. Rare earth elements have excellent chelating properties, easily accept a variety of empty orbitals of multiple ligands, and form coordination bonds with the provided lone pair electrons, thereby terminating the peroxide radicals generated during the combustion process and exerting good flame retardancy 19,20 . Wang et al 21 applied Ni LDHs and rare earth‐doped Ni‐containing LDHs to EVA and found that S–Ni 0.1 MgAl–La has improved dispersion, interface compatibility, and flame retardancy in the EVA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Worse, it releases a large amount of smoke during burning, which poses a serious threat to the safety of life and property. 4,5 Expandable graphite (EG) is a flake graphite compound intercalated by sulfuric acid or nitric acid between the crystal carbon layers of the natural graphite. 6,7 In recent years, EG has received growing attention in the field of flame retardant.…”
Section: Introductionmentioning
confidence: 99%
“…However, EVA is flammable and can continue to burn after catching fire. Worse, it releases a large amount of smoke during burning, which poses a serious threat to the safety of life and property 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation